99mTc-Methionine Hybrid SPECT/CT for Detection of Recurrent Glioma: Comparison With 18F-FDG PET/CT and Contrast-Enhanced MRI. (May 2018) - Arora, Geetanjali; Sharma, Punit; Sharma, Anshul; Mishra, Anil Kumar; Hazari, Puja Panwar; Biswas, Ahitagni; Garg, Ajay; Aheer, Deepak; Kumar, Rakesh
Abstract : Objectives: Posttherapy changes in treated glioma patients cannot be reliably differentiated from tumor recurrence. We evaluated the role of 99m Tc-methionine SPECT/CT for the detection of recurrent glioma and compared the same with 18 F-FDG PET/CT and contrast-enhanced MRI (CeMRI). Methods: Forty-four patients with histologically proven, previously treated glioma and clinical suspicion of recurrence were prospectively enrolled in the study. Of these 44 patients, 39 (28 male and 11 female subjects; age, 38.05 ± 9.7 years) underwent 99m Tc-methionine SPECT/CT, 18 F-FDG PET/CT, and CeMRI of the brain and were included for final analysis. Combination of repeat imaging, biopsy, and/or clinical follow-up (6–36 months) was taken as reference standard. Sensitivity, specificity, positive predictive value, negative predictive value, and accuracy were calculated. Diagnostic values among modalities were compared. Results: Positive predictive value and negative predictive value for 99m Tc-methionine SPECT/CT, 18 F-FDG PET/CT, and CeMRI were 95.6% and 56.2%, 92.3% and 61.5%, and 79.4% and 42.9%, respectively. Sensitivity and specificity for the 3 modalities were 75.9% and 90%, 82.8% and 80%, and 87.1% and 30%. Specificity of 99m Tc-methionine SPECT/CT was significantly higher than that of CeMRI ( P < 0.0001) but not of 18 F-FDG PET/CT ( P = 0.36). No significant difference was seen between the modalities for sensitivity and accuracy. Conclusions: 99m Tc-methionine is a promising tracer for detection of recurrent glioma. Diagnostic values of 99m Tc-methionine SPECT/CT are similar to 18 F-FDG, although it is more specific than CeMRI. So it may be used as a cost-effective alternative and also where PET/CT is not available.